MEANS OF OBJECTIVE ASSESSMENT OF EDUCATIONAL ACHIEVEMENTS OF HIGHER EDUCATION ACQUISITIONS DURING DISTANCE EDUCATION OF ANALYTICAL GEOMETRY - Repeta , Lesia; Kudzinovska , Inna; Repeta , Viktor (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article considers a number of issues covering problems and means of objective assessment of educational achievements in the study of analytical geometry of higher education applicants, organization of methods of control and testing in the distance learning mode.